Пантелеймон Куліш у долі й творчості Михайла Старицького (до постановки проблеми) - Поліщук, В. (Слово і Час, 2021)
У студії докладно проаналізовано життєві і творчі взаємини двох класиків українського письменства ХІХ ст.; визначальний кут зору — «від» М. Старицького. Простежено аспекти як біографічного, так і творчого плану. Зроблено акцент на помітних відмінностях рис характеру і вдачі кожного з письменників. У розгляді типологічних збіжностей і розбіжностей на полі творчості зауважується, що роман «Чорна рада» мав значний і тривалий вплив на формування світогляду, а згодом і підходів молодшого автора до написання прозових творів, зокрема в реалізації пророчого потенціалу Кулішевої хроніки. Приділено увагу дискусійному питанню про те, хто із цих класиків у царині поезії першим почав «ламати шаблони» наслідування Шевченкової манери віршування. На основі аналізу творів М. Старицького виснувано, що їх автор принципово не поділяв поглядів «пізнього» П. Куліша на історичну роль козацтва та гайдамацького руху. The paper focuses on the relationship of two Ukrainian literature classics of the 19th century Panteleimon Kulish and Mykhailo Starytskyi, the viewpoint of the latter being basic in this research. The study reveals some aspects of biographical and then creative nature that had an impact on the outlook of the younger writer (M. Starytskyi). There were noticeable differences in the characters and temperaments of the two writers. The noble tolerance on the part of M. Starytskyi allowed maintaining a constructive dialogue between colleagues, despite the substantial worldview and historiosophical ‘swings’ of P. Kulish in the 1870s and 80s. As to typological convergences and differences in the field of literature, it is noted that P. Kulish’s “Commoners’ Council” (“Chorna Rada”) had a significant and long-lasting impact on Starytskyi’s outlook and subsequently his prose works (especially fiction). The prophetic potential of Kulish’s novel (commoners’ councils as the causes of ‘ruin’, the destructive nature of the thoughtless spontaneity of the masses, the threat of populism, etc.) was realized in Starytskyi’s writings. The study shows that in different spheres of creative work, both P. Kulish and M. Starytskyi tended to innovations and experiments focused on the best achievements of European literatures. Special attention is paid to the debatable issue of the classics’ priority in ‘breaking the patterns’ of imitating Shevchenko’s manner of verse (based on the judgments of I. Franko, M. Zerov, and Ye. Nakhlik). The author of the paper defends the view of at least simultaneous overcoming the mentioned patterns by P. Kulish and M. Starytskyi. Some analytical comments are given to M. Starytskyi’s judgments about T. Shevchenko, contained in his letters to P. Kulish. The analysis of M. Starytskyi’s works (novels, dramas, some poems) shows that their author did not share the views of the late works by P. Kulish concerning the historical role of the Cossacks and haidamak movement.